2015
DOI: 10.1111/vec.12322
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled clinical trial of intravenous lipid emulsion as an adjunctive treatment for permethrin toxicosis in cats

Abstract: The clinical staging system was repeatable and reliable. Clinical stages of permethrin toxicosis in ILE-treated cats improved earlier compared to control cats, suggesting ILE may be a useful adjunctive therapy in the treatment of permethrin toxicosis in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 58 publications
(125 reference statements)
0
39
0
3
Order By: Relevance
“…‐ 162 In particular, Intralipid has been used extensively to treat ivermectin 77 , 163 166 and permethrin 167 170 toxicity. In particular, Peacock et al 171 conducted a randomized trial of lipid emulsion in permethrin toxicosis in felines and found a robust rescue effect of the lipid emulsion in comparison to saline. Beyond that, a number of other overdoses with potential translational relevance have been reported as effectively managed with ILE, including moxidectin, 172 ibuprofen, 173 carbamazepine, 106 , 119 and baclofen 106 .…”
Section: Part Iii: Clinical Futurementioning
confidence: 99%
“…‐ 162 In particular, Intralipid has been used extensively to treat ivermectin 77 , 163 166 and permethrin 167 170 toxicity. In particular, Peacock et al 171 conducted a randomized trial of lipid emulsion in permethrin toxicosis in felines and found a robust rescue effect of the lipid emulsion in comparison to saline. Beyond that, a number of other overdoses with potential translational relevance have been reported as effectively managed with ILE, including moxidectin, 172 ibuprofen, 173 carbamazepine, 106 , 119 and baclofen 106 .…”
Section: Part Iii: Clinical Futurementioning
confidence: 99%
“…Three animal experiments studied ILE for non-LA toxicity. [35,39,42] In one trial, 20 cats with 14 additional controls were exposed dermally to permethrin. ILE was administered to the treatment group at 15 mL/kg as a continuous intravenous infusion over 60 minutes.…”
Section: Non-local Anestheticsmentioning
confidence: 99%
“…A grading system for neurologic effects detected a decrease in the duration and severity of poisoning in the treatment group reported as a decrease in the duration and severity of poisoning in the treatment group. [39] Another randomized experiment in swine sought to determine a difference in mean arterial blood pressure (MAP), QRS duration and survival after diphenhydramine poisoning. Twenty-four animals were equally divided into two groups.…”
Section: Non-local Anestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to investigating the effects and potential benefits of intravenous lipid therapy in cats with a similar toxin, permethrin, Peacock et al report the largest randomized controlled trial in cats. In this trial, investigators chose to evaluate the impact of intravenous lipid therapy on course of clinical signs associated with permethrin toxicity.…”
mentioning
confidence: 99%